Dr. R. Luke Sturgill — Deep Plane Facelift — Carmel - Sturgill, R. Luke (DEEPPLANE™, 2026)
Surgeon profile record for Dr. R. Luke Sturgill, practicing in Carmel, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-002986; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; carmel